A scoping review of national policies for hierarchical medical system in China since the 2009 health reform - Cai, Tingting; Hua, Yuting; Fang, Leyi; Xia, Yunhui; Shen, Jiantong; Lou, Jianlin (Frontiers in Public Health, 2025)
BackgroundUniversal health coverage (UHC) is driving the global health agenda. In 2009, the Chinese government launched a new round of healthcare reform toward UHC, and made remarkable progress in UHC through the establishment of a hierarchical medical system (HMS). We aim to summarize and review the evolution of China’s hierarchical medical system policy.MethodsEligible policies were identified between March 7, 2009 and December 31, 2022, by searching the official websites of the PKULAW Database, the Chinese State Council, and related ministries. Policy screening and data extraction were conducted by two researchers independently and discrepancies were resolved by consensus. Policy maker, policy initiatives, policy instrument, policy structure and evolution were visually analyzed. The people-centered integrated care model was used as the framework for analysis.Results150 policy documents were included, most of which were issued in the 13th Five-Year Plan. There were 14 ministries involved in policy making, and they cooperated with each other, led by the State Council, with the National Health Commission and the National Administration of Traditional Chinese Medicine as the core. The pattern of policy making was top-down and bottom-up. Several areas showed to have strong policy support, including reforming the healthcare service delivery system, strengthening the primary health care workforce, reforming the health insurance system, and digitizing the health care system. Supply-side and environmental policy instruments were used the most while demand-side policy instruments were used the least.ConclusionChina’s hierarchical medical system had completed the transformation from local pilot to national promotion. Based on the results of the study, we propose the following recommendations: (1) a unified policy framework is necessary to coordinate the development and regulation of hierarchical medical system and facilitate multi-sectoral cooperation, (2) in-depth reforms in the key regions in hierarchical medical system, such as public hospital reform, medical insurance payment, (3) balance the use of various policy instruments, giving full consideration to the characteristics of hierarchical medical system at different stages.